Smuggling on controlled items (rice): the law and its enforcement in Malaysia / Siti Nur Fudhliha Ab Aziz and Jamilah Samsudin - Ab Aziz, Siti Nur Fudhliha; Samsudin, Jamilah (2008)
This study is concerning smuggling of controlled items. For this purpose, special reference is made to controlled item of rice. The dissertation in this study will focuses more on the law and its enforcement. Therefore, to emphasize the discussion on the issues, comparative analyses have been made between Malaysia and other countries i.e. Thailand, Singapore, China and Philippines. Furthermore, the observation also has been made to the approaches taken by those countries in controlling such matters. This was done by looking at the countries' statutes that govern the controlled items i.e. paddy or rice as was explained in Chapter II and III of this research study. Chapter I is basically about the introduction and which aspect that this research focus on. On other hand, Chapter II give details about the legislation in Malaysia in dealing with the issue of smuggling of controlled items i.e. paddy or rice. Chapter HI is on comparison of the legislation and enforcement in other countries i.e. Thailand, Singapore, China and Philippines. The last chapter is about recommendations and conclusion of the study.